PENGEMBANGAN "BATITA" (BACA AT-TIN DAN TAJWIDNYA) BERBASIS PPT INTERAKTIF TENTANG MEMBACA SURAH AT-TIN PADA PEMBELAJARAN PAI KELAS IV SD - Nurkholizah, Dede Fitri; Yulianti, Nery; Azizah, Lu'lu'ul; Aeni, Ani Nur (Jurnal Dedikasi Pendidikan, 2024)
The problem found in this study is there are still students who are not fluent in reading the Qur’an so that it becomes an obstacle when reading short surah correctly. This study aims to determine the results of the BATITA (Baca At-Tin dan Tajwidnya) product trial based on Interactive PPT which is expected to help students in learning short surahs. The research method used is the design and development [l1] method with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at SDN Sukasari on grade IV students totaling 30 people. In addition, this study also involved PAI subject teachers as material expert validators and SPAI lecturers as media experts. The results of the study obtained a product assessment from media experts of 95% (Very Good), from material experts 98% (Very Good), and from students obtained a score of 91,6% (Very Good). Thus, it can be concluded that the BATITA (Baca At-Tin dan Tajwidnya) interactive PPT is suitable for use in the learning process